Flow in the Workplace: Experiencing Flow among Employees of Rehabilitation Centers (Zien Journal of Social Sciences and Humanities, 2023)
The aim of the study was to explore the flow experience among employees of rehabilitation centers (N = 90) in Tbilisi, Georgia, with respect to variables such as subjective happiness and self-undermining behavior. Correlational analysis revealed significant relationships between the three variables, while regression analysis showed that both self-undermining behaviors and subjective happiness significantly predicted flow perception at workplace. Flow was negatively related to self-undermining, while it had positive link with subjective happiness.